1996
DOI: 10.1007/s003840050065
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting recurrence in Crohn's disease

Abstract: It has been suggested that certain clinical and morphological features can modify the outcome of Crohn's disease, particularly regarding recurrence after surgery. A series of 233 patients was followed prospectively. They underwent a resectional surgical procedure for both primary and recurrent Crohn's disease during a fifteen-year period with a minimum follow-up of eighteen months. Possible risk factors for recurrence were studied. They included duration of disease before primary surgery, the type of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 28 publications
0
50
1
5
Order By: Relevance
“…Age: Subjects with a diagnosis of CD at a young age have higher rates of recurrence in some studies [14,15] but neither in others [16,17] nor in the present study.…”
Section: Patient Related Factorscontrasting
confidence: 68%
“…Age: Subjects with a diagnosis of CD at a young age have higher rates of recurrence in some studies [14,15] but neither in others [16,17] nor in the present study.…”
Section: Patient Related Factorscontrasting
confidence: 68%
“…It has been suggested that several factors influence post-operative recurrence rates, including the duration of the disease before resection, smoking, pre-operative lymphopenia, the type of surgery, the site of Crohn’s disease, and the type of Crohn’s disease – perforating vs. non-perforating disease as well as the use of medications [3,4,5,6,7,8,9,10,11,12]. Some of the studies reported conflicting results regarding these factors.…”
Section: Introductionmentioning
confidence: 99%
“…La recurrencia de la enfermedad en la zona de la anastomosis ileocolónica se produjo a los 7 y 11 años de la primera operación por EC, lo cual evidencia que a los 5 años en nuestra serie no se observaron recidivas que necesitaron de tratamiento quirúrgico, cifra que es menor a las publicadas [18][19][20] . Es necesario destacar que en esta serie no hubo un seguimiento endoscópico y/o radiológico protocolizado, de manera que pudo haber habido pacientes asintomáticos con recidiva endoscópica de la enfermedad que no se manifestaron clínicamen-te o que respondieron al tratamiento médico evitando así el tratamiento quirúrgico.…”
Section: Discussionunclassified
“…Así entonces, en esta serie, la cifra de recurrencia después de RIC de 7% a 9,5 años comprende la recurrencia clínica, demostrada radiológica o endoscópicamen-te con indicación operatoria. Usando un criterio similar, en otras series la prevalencia de recurrencia a 5 años en pacientes sometidos a cirugía por EC es de 13 a 24% [18][19][20] . El porcentaje de recurrencia es aún mayor, al realizar un seguimiento a más de 10 años desde la operación 21 .…”
Section: Discussionunclassified